2013
DOI: 10.1200/jco.2013.50.7061
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Problems of Teenagers Who Have a Parent With Cancer: A Population-Based Case-Control Study (Young-HUNT Study)

Abstract: In this population-based study, teenagers who had a parent with cancer did not have higher prevalence of psychosocial problems than controls. Sex differences observed in previous clinically based studies were confirmed but may simply reflect sex differences observed among teenagers in general.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 32 publications
(23 reference statements)
1
23
0
Order By: Relevance
“…This finding also supports the previous study showing that children express elevated stress response symptoms after a parental cancer diagnosis . Our study corroborates previous studies in demonstrating that parental cancer was associated with a higher risk of affective and anxiety disorders, predominantly in females . Clear associations were also found between parental cancer and use of antidepressants, anxiolytics, and hypnotics and sedatives.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding also supports the previous study showing that children express elevated stress response symptoms after a parental cancer diagnosis . Our study corroborates previous studies in demonstrating that parental cancer was associated with a higher risk of affective and anxiety disorders, predominantly in females . Clear associations were also found between parental cancer and use of antidepressants, anxiolytics, and hypnotics and sedatives.…”
Section: Discussionsupporting
confidence: 92%
“…35 Our study corroborates previous studies in demonstrating that parental cancer was associated with a higher risk of affective and anxiety disorders, predominantly in females. 4,36 Clear associations were also found between parental cancer and use of antidepressants, anxiolytics, and hypnotics and sedatives. The higher risk of use of hypnotics and sedatives may otherwise reflect an increased susceptibility to sleep disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Only four studies had a control group, and Huizinga, van der Graaf, Visser, Dijkstra, and Hoekstra‐Weebers () used the background population as control. In most studies, somatic symptoms were registered as a part of identifying psychosocial problems in children (Dyregrov & Dyregrov, ; Huizinga et al, ; Huizinga et al, ; Huizinga et al, ; Jeppesen, Bjelland, Fossa, Loge, & Dahl, ; Kucukoglu & Celebioglu, ). The data were primarily questionnaire‐ and interview‐based, and several different designs were applied (Table ); thus a meta‐analysis of the results was not conducted due to lacking comparability of the outcome data.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were specific about the types of symptoms measured, but four studies (Huizinga et al, ; Huizinga et al, ; Jeppesen et al, ; Kucukoglu & Celebioglu, ) reported somatic problems without specifying complaint categories (see Table ).…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, better family functioning or family environment seem to correlate with higher levels of positive adjustment in cancer patients' children [13]. Jeppesen et al [14] in their case-control study of children with or without a parent diagnosed with cancer found no significant differences between the two groups in terms of overt psychosocial problems. Their results contradict the theory of trauma and could rather be interpreted in the context of the theory of resilience [15][16][17].…”
mentioning
confidence: 89%